Integrando sistemas de informação via serviço web: um estudo de caso na defesa civil de Rio Claro - Affonso, Frank José [UNESP]; Carneiro, Maria Cecilia Vecchiato Saenz [UNESP]; Carneiro, José Gustavo Viegas; Kuroishi, Danilo de Almeida; Polezi, Luiz Afonso; Benato, Gabriele Salgado [UNESP]; Fernando, Filipe Alves de [UNESP]; Carvalho, Veronica Oliveira de [UNESP]; Govone, José Silvio [UNESP]; Nourani, Farid [UNESP]; Falcão, Jorge Gustavo [UNESP]; Cattani, João Gabriel Zupi [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
According to PRESSMAN (2006), SOMMERVILLE (2011), a computer system can assist in the elaboration of daily tasks, accelerating their execution and providing better control about them. In this sense, a System for Occurrence Management (SOM) for the Rio Claro’s Civil Defense was developed. In short, this system aims to support the Civil Defense in the attendance of the occurrences. Next, a System for Occurrence Georeferencing (SOG) in Rio Claro city and region was also developed. This system aims to map the type of occurrence by addresses, plotting some types of maps. For instance, occurrences by one or more neighborhoods, type of occurrences and so on. Based on the presented context, this paper presents an integration process by means of web service of both systems (i.e., SOM and SOG). As result, it is expected that such integration can help both the Civil Defense and the public manager in their decisions and actions in favor of the population of the Rio Claro city and region.

De acordo com PRESSMAN (2006), SOMMERVILLE (2011), um sistema computacional pode auxiliar na elaboração das tarefas do dia-adia, podendo acelerar sua execução e propiciar melhor controle sobre as mesmas. Neste sentido, um Sistema Computacional para Gerenciamento de Ocorrências para a Defesa Civil de Rio Claro (SC4GO-DC) foi desenvolvido. Esse sistema visa apoiar a Defesa Civil de Rio Claro no atendimento de ocorrências. Em seguida, um Sistema Computacional para Georreferenciamento de Ocorrências (SC4Georref) também foi elaborado. Esse sistema visa mapear a cidade de Rio Claro em relação às ocorrências registradas. Por exemplo, localização e tipo de ocorrência são informações que podem ser visualmente plotadas em mapas por esse sistema. Portanto, diante do projeto desses dois sistemas, este artigo visa apresentar um processo de integração via serviço web. Como resultado, espera-se que essa integração possa auxiliar tanto a Defesa Civil quanto o gestor público na tomada de decisões e execução de ações em prol da população da cidade de Rio Claro e região.
Keywords: System integration; Web service; Computer system; Integração de sistemas; Serviço web; Sistema computacional